Decoration of Citrus limon wood carbon with Fe3O4 to enhanced Cd2+ removal: A reclaimable and magnetic nanocomposite. (November 2021) - Peighambardoust, Seyed Jamaleddin; Foroutan, Rauf; Peighambardoust, Seyed Hadi; Khatooni, Hamzeh; Ramavandi, Bahman
Abstract: In the present study, the activated carbon of lemon (ACL) was generated from Citrus limon wood waste and composited with Fe3 O4 nanoparticles. The ACL/Fe3 O4 magnetic composite was effectively used to eliminate Cd 2+ from an aqueous solution. The active surface area values for ACL and ACL/Fe3 O4 magnetic composite were 25.99 m 2 /g and 38.70 m 2 /g, respectively indicating the effectiveness of Fe3 O4 nanoparticles in improving ACL active surface area. The response surface methodology with central composite design (RSM-CCD) was used to determine optimal values of pH, ACL/Fe3 O4 dose, contact time, and Cd 2+ concentration on the decontamination efficiency. The Langmuir and Freundlich isotherm models had more potential to describe the adsorption process using ACL and ACL/Fe3 O4, respectively. The Langmuir-based adsorption capacity was obtained as 28.2 mg/g (ACL) and 39.6 mg/g (ACL/Fe3 O4 ). A pseudo-second order (PSO) model was successfully applied to evaluate the adsorption process kinetic behavior. A higher value of α parameter for ACL/Fe3 O4 (5.7 mg/g.min) than that of ACL (3.5 mg/g.min) indicated that the magnetic composite had a greater tendency to absorb Cd 2+ . In addition, the Weber–Morris model showed that various mechanisms such as intraparticle diffusion and boundary layer effects may have a role in the adsorption process. The study of ad(de)sorption behavior showed that the adsorbents have a good ability to adsorb Cd 2+ and no significant change in their performance has been made up to 4 times of reuse. Our results showed that ACL modification using Fe3 O4 nanoparticles improved the adsorption efficiency of ACL to remove Cd 2+ from the aqueous solutions. Graphical abstract: Image 1 Highlights: The lemon activated carbon (ACL) was decorated with iron to produce ACL/Fe3 O4 . The BET values for ACL and ACL/Fe3 O4 were 25.9 m 2 /g and 38.7 m 2 /g, respectively. The Cd removal by ACL and ACL/Fe3 O4 followed Langmuir and Freundlich, respectively. The process kinetic behavior was described by pseudo-second order model. The α value for ACL/Fe3 O4 (5.7 mg/g.min) was greater than that of ACL (3.5 mg/g.min).